Comparison of using NaOH and KOH activated fly ash-based geopolymer on the mechanical properties - Abdul Rahim, R.H. (Trans Tech Publications Ltd, 2015)
Geopolymer synthesis has two main requirements to fulfil which are the source material that is rich in Silicon (Si) and Aluminum (Al) and alkali activator such as sodium/potassium hydroxide. Sodium hydroxide (NaOH) is widely used for the synthesis of geopolymer compared to potassium hydroxide (KOH) with addition of silicate solution for the purpose of increasing dissolution process. However, the comparison of using different activator in the absence of silicate solution for geopolymer synthesis is not well established. This paper presents an evaluation on compressive strength of fly ash-based geopolymer by using different activator (KOH and NaOH) with respect to different curing conditions (time and temperature) in the absence of sodium silicate. The samples were mixed using mortar mixer and prepared in 50mm Ã 50mm Ã 50mm mould for determination of compressive strength. It can be observed that the highest compressive strength up 65. 28 MPa was obtained using NaOH. Meanwhile, synthesis using KOH only recorded 28. 73 MPa. The compressive strength was better when cured at elevated temperature (60Â°C) than room temperature (25Â°C). Further analysis on the microstructure of the highest compressive strength geopolymer samples for both activators was carried out using Field Emission Scanning Microscopy (FESEM) and Raman spectroscopy. Â© (2015) Trans Tech Publications, Switzerland.